Short luteal phases and ovulations without oestrus in primiparous Borana (Bos indicus) cows in the central highlands of Ethiopia - Tegegne, Azage; Geleto, A.; Kassa, T. (Elsevier, 1993)
The incidence of short luteal phases and ovulations without oestrus was investigated in 42 primiparous Borana cows. Based on calving body weight, cows were allocated to either a control group with grass hay only or to a supplement group with a concentrate ration. Within nutritional groups, cows were further assigned to either milked or partially suckled groups. Cows were under continous observation and vasectomised teaser bulls used in oestrus detection. Blood samples were collected twice weekly commencing on Day 30 postpartum until pregnancy for determination of plasma progesterone levels. A progesterone concentration of above 1 ng ml was taken as a cut-off value between luteal and non-luteal phases and oestrous cycles of 17 days or less were considered as short. By 150 days postpartum, ovarian cycle activity had commenced in 64.3 percent of the cows while 35.7 percent remained anoestrons. There were no nutritional and suckling influences on the incidence of ovulation without oestrons and short luteal phases. Progesterone concentrations, however, were lower in short than in normal oestrus cycles. It was concluded that although short luteal phases occured in a relatively larger proportion of cows, it was not an exclusive prerequisite for the establishment of normal oestrons cycles.